2008
DOI: 10.1016/j.jmb.2008.09.063
|View full text |Cite
|
Sign up to set email alerts
|

Hsp104 Targets Multiple Intermediates on the Amyloid Pathway and Suppresses the Seeding Capacity of Aβ Fibrils and Protofibrils

Abstract: The heat shock protein Hsp104 has been reported to possess the ability to modulate protein aggregation and toxicity and to "catalyze" the disaggregation and recovery of protein aggregates, including amyloid fibrils, in yeast, Escherichia coli, mammalian cell cultures, and animal models of Huntington's disease and Parkinson's disease. To provide mechanistic insight into the molecular mechanisms by which Hsp104 modulates aggregation and fibrillogenesis, the effect of Hsp104 on the fibrillogenesis of amyloid beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 50 publications
7
54
1
1
Order By: Relevance
“…Because no binding of A␤ monomer to BRICHOS was detected, it is likely that BRICHOS instead binds to assemblies formed early in the aggregation processes. The chaperones Hsp104, Hsp70, and Hsp40 are active at substoichiometric amounts and preferentially interact with intermediates formed in the fibril formation process (13,14). In overexpressing cell lines, Hsp70 protects against A␤ 42 -induced neuronal death (60), whereas ␣B-crystallin, Hsp27, Hsp20, and HspB2/B3 reduce A␤ cell toxicity (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because no binding of A␤ monomer to BRICHOS was detected, it is likely that BRICHOS instead binds to assemblies formed early in the aggregation processes. The chaperones Hsp104, Hsp70, and Hsp40 are active at substoichiometric amounts and preferentially interact with intermediates formed in the fibril formation process (13,14). In overexpressing cell lines, Hsp70 protects against A␤ 42 -induced neuronal death (60), whereas ␣B-crystallin, Hsp27, Hsp20, and HspB2/B3 reduce A␤ cell toxicity (61).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular chaperones have evolved to counteract misfolding in the cell. Examples are the heat-shock proteins (Hsp) 70, Hsp90, and Hsp104 (13)(14)(15)(16) and * This work was supported by the Swedish Research Council.…”
mentioning
confidence: 99%
“…Surprisingly, no metazoan homolog or analog of Hsp104p has been identified; such unique disaggregation activity is restricted to bacteria, fungi, and plants. Several attempts were made to introduce the wellcharacterized yeast HSP104 gene in rodent models of neurodegenerative disorders (Vacher et al 2005;Perrin et al 2007;Arimon et al 2008;Lo Bianco et al 2008). These reports showed that Hsp104 was able to reduce aggregation rates for various amyloids and even prolong the lifespan of a Huntington disease mouse model by 20% (Vacher et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hsp104 has been shown to convert an aggregated and protease resistant mammalian prion-like protein fragment of PrP Sc into a random coiled structure (Schirmer andLindquist 1997, Liu et al 2011). Additionally, Hsp104 inhibits the seeding properties of Abeta fibrils (Arimon et al 2008), and is effective against protein aggregation (Mosser et al 2004). Furthermore, the overexpression of Hsp104 in transgenic mice expressing the first 171 residues of mutant huntingtin, used as a model for Huntington's disease, reduced the formation of aggregates and prolonged the lifespan of the animals (Vacher et al 2005).…”
Section: Yeast Hsp104 a Molecular Chaperone Involved In The Recoverymentioning
confidence: 99%